Research and Development Investment: The Role of Corporate Governance and Financial Slack - Erlin Ketna Purnamasari; Marfuah; Priyono Puji Prasetyo (Jurnal Aplikasi Bisnis, 2025)
Abstract This study aims to examine and develop an understanding of the effect of corporate governance and financial slack on R&D investment by exploring the influence of ownership structure and board characteristics which consequently can influence the expansion or reduction of a company's R&D budget. Using the purposive sampling method, 41 samples of pharmaceutical companies were selected which were listed on the IDX in 2013-2019. The results of hypothesis testing concluded that managerial ownership, tenure of independent commissioners, and financial slack proved to have a significant positive effect on R&D investment decisions. Meanwhile, institutional ownership, the proportion of independent commissioners, educational level of directors, and education of directors do not have a significant influence on R&D investment decisions in pharmaceutical companies in Indonesia. The results of this study indicate that the management ownership structure and the characteristics of independent commissioners are elements of corporate governance that are able to play a role in aligning the interests of management and shareholders in making R&D investment decisions in pharmaceutical companies in Indonesia. In addition, this study also found that R & D investment tends to increase when companies have large financial slack. The results of this study contribute to management in making better R&D investment decisions. Keywords: Corporate Governance; Financial Slack; Managerial Ownership; R & D investment Abstrak Penelitian ini bertujuan untuk mengkaji dan mengembangkan pemahaman tentang pengaruh antara corporate governance dan financial slack terhadap investasi R&D dengan mengeksplorasi pengaruh struktur kepemilikan dan karakteristik dewan yang konsekuensinya dapat mempengaruhi perluasan atau pengurangan anggaran R&D perusahaan. Dengan menggunakan metode purposive sampling, terpilih 41 sampel perusahaan Farmasi yang terdaftar di BEI tahun 2013-2019. Hasil pengujian hipotesis menyimpulkan bahwa kepemilikan manajerial, masa jabatan komisaris independen, dan financial slack terbukti berpengaruh positip signifikan terhadap keputusan investasi R&D. Sementara kepemilikan institusional, proporsi komisaris independen, tingkat pendidikan direksi, dan bidang pendidikan direksi tidak memiliki pengaruh signifikan terhadap keputusan investasi R&D pada perusahaan farmasi di Indonesia. Hasil penelitian mengindikasikan bahwa struktur kepemilikan manajemen, dan karakteristik komisaris independen merupakan unsur corporate governance yang mampu berperan dalam mensejajarkan kepentingan antara manajemen dan pemegang saham dalam pembuatan keputusan investasi R &D pada perusahaan Farmasi di Indonesia. Selain itu penelitian ini juga menemukan bahwa investasi R & D cenderung meningkat ketika perusahaan mempunyai slck financial yang besar. Hasil penelitian ini memberi kontribusi bagi manajemen dalam membuat keputusan investasi R &D yang lebih baik. Kata Kunci:Corporate Governance; Financial Slack; Kepemilikan Manajerial; Investasi R & D